2004
DOI: 10.1111/j.1399-0012.2004.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastroparesis following kidney/pancreas transplant

Abstract: This pilot study examined associations among patterns of gastric myoelectrical activity, symptoms of gastroparesis, years of diabetes, months of dialysis, and use of gastrointestinal medications in gastroparetic kidney-pancreas (KP) transplant recipients. Electrogastrography (EGG) and gastric symptom data were obtained from 42 transplant recipients before and after transplant (6, 12, and 24 months). Recipients were 38 +/- 7 yr of age, 88% Whites, and 60% male; 97% had hypertension. All had functioning grafts p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Pancreas transplants prevent progression of such preexisting diabetic complications as neuropathy or retinopathy, but evidence on the benefits of this intervention in diabetic gastroparesis is conflicting. Investigators in one report concluded that, although symptoms may decrease after pancreas/kidney transplant, gastroparesis remains a challenging problem [47].…”
Section: Other Operative Interventionsmentioning
confidence: 99%
“…Pancreas transplants prevent progression of such preexisting diabetic complications as neuropathy or retinopathy, but evidence on the benefits of this intervention in diabetic gastroparesis is conflicting. Investigators in one report concluded that, although symptoms may decrease after pancreas/kidney transplant, gastroparesis remains a challenging problem [47].…”
Section: Other Operative Interventionsmentioning
confidence: 99%
“…Unfortunately, extraintestinal complications developed in three patients, two of whom died; thus, the benefits of the procedure were not clearly demonstrated. Likewise, studies report conflicting data on the benefits of pancreatic transplantation in patients with diabetic gastroparesis [94].…”
Section: Other Operationsmentioning
confidence: 99%
“…Jejunostomies are indicated to maintain fluid balance and nutritional status,92 and can be an effective “last resort” measure 92. Interestingly, pancreatic transplantation has been shown to benefit those with DG 94. Studies assessing neuropathy have shown early nerve fiber regeneration in type 1 diabetic patients after pancreas transplantation,95 and this may be the potential basis for relieving symptoms, but of course, overall improved glycemic control must play a role in improving gastric emptying.…”
Section: Mechanical Therapiesmentioning
confidence: 99%